Producciones cerámicas en la Mértola islâmica - Gómez Martínez, Susana (2003)
Mértola used to play an important role in international commercial traffic as the last port on the River Guadiana. Ceramics decorated in green and manganese, in “cuerda seca” and graffiti have arrived there. Stylistic, formal analysis, supported by analyses of the pastes, allow us to suppose that various centrs producing these ceramics existed. It is very likely that, in the 12th century, Almeria was a centre that supplied “cuerda seca” ceramic and graffiti ceramics. Other series of ceramic have a more doubtful origin. The green and manganese could have been produced in various places amongst wich Málaga or Mértola ifself.